Pulmonary ossification: a case report - Di Somma, C.; Annunziata, A.; Coppola, A.; Polistina, G. E.; Marotta, A.; Fiorentino, G. (Frontiers in Medicine, 2025)
Pulmonary calcification and ossification are uncommon findings characterized by the deposition of calcium salts or bone tissue in the lung, generally associated with chronic kidney disease, hyperparathyroidism, and several other causes (1). Ossification is bone formation without or with marrow elements in the lung (1). In some patients, a new entity of subclinical primary hyperparathyroidism has been detected, characterized by persistently elevated parathyroid hormone concentration and normal serum calcium level, usually asymptomatic (2). CT scan is the standard method for detecting calcification and ossification. Radiological presentation on CT is characterized by round or lobulated nodules (3). Follow-up consists of monitoring lung images and lung function to assess disease progression. It suggests an annual CT scan. In this case, we presented a rare association of dendriform ossification with normocalcemic hyperparathyroidism, in particular, in a patient with pulmonary ossification, subclinical primary hyperparathyroidism, and diffuse calcifications.